Determinants of access to rural financing in the democratic republic of Congo: The case of Kongo central - Mandiangu, Israel; Mapapa, Augustin Mbangala; Cornet, Annie; Burny, Philippe; Lebailly, Philippe (Asian Development Policy Review, 2024)
This article aims to identify the determinants influencing access to rural finance, focusing on a sample of 500 family farms in Kongo Central. This study revealed that membership in a financial solidarity group and awareness of the existence of a local development committee significantly influences access to credit using Probit and Logit regression methods. This study highlights the importance of supply and demand factors in accessing rural finance. Key demand-related determinants include gender, marital status, sector of activity, household size and high levels of education. This research suggests strengthening policies aimed at increasing financial education and women's empowerment to improve access to financing. These measures could enable more individuals especially women to effectively access and use financial services. By addressing these determinants can help policymakers better design interventions to support rural development in this province. The results underscore the need for a holistic approach considering both supply and demand factors to improve financial inclusion for rural populations.